The Cultural and Historical Trail Map of Peranakan Heritage in the Andaman Provincial Cluster in Thailand - Thippiroon Poomduang (Institut Pertanian Bogor, 2021)
This study explored the trace of Peranakan heritage in the Andaman provincial cluster and presented the Cultural and Historical Trail Map of Peranakan heritage in Andaman provincial cluster. The concept of development communication objectives was used to create a research framework. Research results in the